2022
DOI: 10.3390/vaccines10010101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Transplacental Antibody Transfer in SARS-CoV-2-Immunized Pregnant Women

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during pregnancy could result in adverse perinatal outcome. Clinical data on the assessment of the immune response in vaccinated pregnant women and subsequent transplacental antibody transfer are quite limited. Objective: To assess maternal and neonatal neutralizing antibody levels against both wildtype and Delta (B.1.617.2) variants after maternal mRNA vaccination. Study Design: This cohort study was conducted 29 pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…An increase in maternal SARS-CoV-2 IgG antibody response with a second dose in pregnancy was also documented by a study that found significantly higher maternal IgG concentrations, week by week, starting two weeks after the first vaccine dose, as well as between the first and second weeks after the second vaccine dose (P<0.005 and P=0.019, respectively) 47. Another study also found higher antibody concentrations during pregnancy after two doses compared with one dose of Moderna vaccine 52…”
Section: Covid-19 Vaccinesmentioning
confidence: 67%
See 1 more Smart Citation
“…An increase in maternal SARS-CoV-2 IgG antibody response with a second dose in pregnancy was also documented by a study that found significantly higher maternal IgG concentrations, week by week, starting two weeks after the first vaccine dose, as well as between the first and second weeks after the second vaccine dose (P<0.005 and P=0.019, respectively) 47. Another study also found higher antibody concentrations during pregnancy after two doses compared with one dose of Moderna vaccine 52…”
Section: Covid-19 Vaccinesmentioning
confidence: 67%
“…Our review identified 20 studies evaluating the immunogenicity of covid-19 vaccines in pregnancy (table 2). 3536373839404142434445464748495051525354 Most studies evaluated immunogenicity of the Pfizer-BioNTech vaccine. A few studies did not clearly describe either the vaccine platform or the total number of participants; however, when described, this information is provided in table 2.…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%
“…Maternal vaccination during pregnancy provides this passive immunity [ 5 , 8 , 12 ]. Several studies reported anti-SARS-CoV-2 vaccine-elicited antibodies in umbilical cord blood and breastmilk after maternal vaccination [ 13 , 14 , 15 ]. To our knowledge, this is the first description of maternal antibodies directly in the amniotic fluid elicited by the COVID-19 vaccine during gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Passive immunity depends on multiple factors, including maternal specific antibody levels and immune response dynamics, as well as the timing of vaccination for the IgG transfer across the placenta during gestation [ 8 ]. Full maternal immunization during pregnancy has been shown to maximize transplacental antibody transfer, with adequate seroprotection in young infants [ 13 ]. Protective antibodies elicited by maternal COVID-19 vaccination in newborns’ cord blood persisted in infants for at least six months [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is essential for protecting pregnant women and their offspring from SARS-CoV-2 infection. Studies have shown that vaccinated women have significantly reduced COVID-19 infection during pregnancy compared with unvaccinated women [ 56 ] and that vaccination provides partial protection for pregnant women and their offspring, even in the face of some variants [ 57 ]. However, additional data are needed to determine how much these antibodies can protect newborns.…”
Section: Maternal Antibody Transfer After Sars-cov-2 Vaccinationmentioning
confidence: 99%